Analysis of Quarter Life Crisis in Final Semester Students In Universitas PGRI Semarang - vita rokhimatul ula,; efriyani sumastuti,; shofif sobaruddin akbar, (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The role of this study is to explore the quarter-life crisis among the final-year students of Universitas PGRI Semarang. This type of study uses mathematic and statistical techniques for the evaluation process and is therefore categorized as quantitative. This study’s population covers only the students who enrolled during the academic years 2018–2020 at Universitas PGRI Semarang. Finally, 350 students were used in the study having used the Slovin formula and purposive sampling as the sample technique. To answer the key questions of this study, this research utilizes the list of the questionnaire responses obtained from the respondents, and SmartPLS 03 software is used. The study shows that the level of self-efficacy affects the Quarter Life Crisis of final-year students of Universitas PGRI Semarang; conversely, the level of self-awareness does not affect Quarter Life Crisis; the level of social support also has an impact on the Quarter Life Crisis; the level of emotional intelligence also affected the Quarter Life Crisis.